Lived experiences of selected househusbands in San Jose, Antique from family breadwinners to stay-at-home fathers - Lavega, Marie Louisse Ynez U.
The study was conducted to identify the factors that led to role reversals between husbands and wives, describe the 24-hour activities performed by househusbands, and describe the meanings househusbands ascribe to their relationship with their wives and children, and to describe the feelings they feel about themselves as primary caregivers. Ten (10) househusbands served as the participants in the study. They should at least have a one-year experience as the primary caregiver and their wives as the primary provider of the family. An in-depth interview questionnaire, a sentence completion test, and a household checklist were utilized in the study. Results of the study revealed that househusbands usually perform male-oriented tasks and exhibit traditional gender ideologies despite exposures to female-oriented tasks. It was also found out that most househusbands have positive relationship with their wives and children.